Quantifying and combating zoonotic viruses poised for emergence: Using multiplex receptor screening and decoy engineering technologies - Alex Odoom; Eugene M. Obeng; Christian K. O. Dzuvor (Proceedings of the National Academy of Sciences, 2026)
Viral discovery efforts have uncovered millions of zoonotic viruses across multiple continents, listed on the World Health Organization’s pandemic risk register. Over two-thirds of these zoonotic viruses pose significant risks, are poised to infect humans, and expose the limitations of current reactive countermeasures, such as vaccines, monoclonal antibodies, and small-molecule antivirals. To mediate infection, these viruses must undergo significant adaptation and exploit specific receptors on human cells, causing “spillover events.” Identifying which human receptors these zoonotic viruses utilize is crucial for assessing spillover risk, understanding viral tropism, and preparing for emergence—ultimately providing insights for pandemic preparedness, development of new antiviral therapeutics, and potentially saving many lives. However, we hypothesize that these advances will require a systemic understanding and scalable platform technologies on an unprecedented scale. Therefore, we propose and evaluate a new and unique paradigm shift toward proactive antiviral interventions centered on host-identified multivalent “decoy” receptor therapeutics that can impose high evolutionary barriers to resistance, even in convergent evolution scenarios. Specifically, we introduce a unified framework that integrates unique, unbiased high-throughput or multiplex receptor screening platforms with AI–driven design to guide the de novo engineering of pandemic-ready broad-spectrum decoys. We also discuss prominent modular engineering strategies that can translate mere molecular affinities into the avidity necessary for potent pan-viral prophylaxis and therapy. The overall integrated pipeline proposed is expected to facilitate the preemptive development of robust countermeasures that will fundamentally reshape our approach to quantifying and combating known and future zoonotic viral threats.